2018
DOI: 10.5114/wo.2018.73879
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase inhibition in cancers: possible tools and targets

Abstract: Heme oxygenase-1 (HO-1, encoded by HMOX1) through degradation of pro-oxidant heme into carbon monoxide (CO), ferrous ions (Fe2+) and biliverdin, exhibits cytoprotective, anti-apoptotic and anti-inflammatory properties. All of these potentially beneficial functions of HO-1 may play an important role in tumors’ development and progression. Moreover, HO-1 is very often upregulated in tumors in comparison to healthy tissues, and its expression is further induced upon chemo-, radio- and photodynamic therapy, what r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 106 publications
1
76
0
Order By: Relevance
“…HO-1 is a key enzyme in the antioxidant response of tubular cells, and upregulation of HO-1 protects mitochondrial function [24]. Previous reports demonstrated that HO-1 is upregulated in response to oxidative stress in proximal tubular cells where it confers significant cytoprotective and antiinflammatory effects [5,7]. Our results indicated that HO-1 was upregulated with 5-ALA/AFC in mProx24 cells, suggesting that it might play a key role in the survival of 5-ALA/SFC-treated cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 is a key enzyme in the antioxidant response of tubular cells, and upregulation of HO-1 protects mitochondrial function [24]. Previous reports demonstrated that HO-1 is upregulated in response to oxidative stress in proximal tubular cells where it confers significant cytoprotective and antiinflammatory effects [5,7]. Our results indicated that HO-1 was upregulated with 5-ALA/AFC in mProx24 cells, suggesting that it might play a key role in the survival of 5-ALA/SFC-treated cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is an inducible form of HO whose upregulation generates cytoprotective products, such as bilirubin and CO [6]. HO-1 is thought to exert its protective effects in the kidney by degrading heme, a pro-oxidant, and producing anti-inflammatory, antioxidant, and anti-apoptotic metabolites [7]. 5-aminolevulinic acid (5-ALA), commonly found in plants, bacteria, fungi, and animals, is a precursor to biosynthetic tetrapyrroles, including chlorophyll, vitamin B12, and heme [8].…”
mentioning
confidence: 99%
“…Compared to CUR, the structure of DMC lacks one methoxy group directly linked to the benzene ring, as shown in Figure 1A. To investigate the pharmacological potential of DMC against OSCC, we examined short-term (24 h) and long-term treatment (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days) effects of DMC on the cell growth of primary SCC-9 and metastatic HSC-3 OSCC cells, respectively using thiazolyl blue tetrazolium bromide (MTT) and colony formation assays. As shown in Figure 1B, after 24 h, DMC treatment concentration dependently inhibited the cell proliferation of both OSCC cells, and the 50% growth inhibitory concentration (IC50) was around 50 µM.…”
Section: Dmc Exerts Antiproliferative Activity and Causes G2/m Cell Cmentioning
confidence: 99%
“…Heme oxygenase-1 (HO)-1 protein, in non-neoplastic cells, is encoded by an stress-inducible gene (HMOX1) but, as soon as it has been translated, the protein is active to degrade heme to biliverdin, carbon monoxide (CO), and free iron [10]. HO-1 was reported to be overexpressed or downregulated in different cancer types and has a multifaceted role in cancer development through regulating apoptosis, angiogenesis, and metastasis [11]. For example, the overexpression of HO-1 can enhance the proliferative or metastatic abilities of pancreatic cancer [12], melanomas [13], and rhabdomyosarcomas [14] in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that all those beneficial features of HO-1 are indispensable for not only normal but also for tumor cells. The regulatory role of HO-1 in tumor cell proliferation, survival, and metastasis has been confirmed in numerous types of cancer (reviewed in [14,15]). Interestingly, Frezza et al have demonstrated that the silencing of HMOX1 in FH-deficient cell lines resulted in their synthetic lethality [16].…”
Section: Introductionmentioning
confidence: 98%